2016
DOI: 10.1186/s13046-016-0427-7
|View full text |Cite
|
Sign up to set email alerts
|

TIMP1 is a prognostic marker for the progression and metastasis of colon cancer through FAK-PI3K/AKT and MAPK pathway

Abstract: BackgroundTissue inhibitor matrix metalloproteinase 1 (TIMP1) plays a vital role in carcinogenesis, yet its precise functional roles and regulation remain unclear. In this study, we aim to investigate its biological function and clinical significance in human colon cancer.MethodsWe analyzed the expression of TIMP1 in both public database (Oncomine and TCGA) and 94 cases of primary colon cancer and matched normal colon tissue specimens. The underlying mechanisms of altered TIMP1 expression on cell tumorigenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
184
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(210 citation statements)
references
References 30 publications
20
184
2
4
Order By: Relevance
“…To further investigate the cause, focus was placed on the apoptosis signaling pathway. It has been reported that apoptosis is related to Akt activation in many cancers and targeting the PI3K/Akt pathway may suppress tumorigenesis and induce cell death . As shown, treatment combining hyperthermia and RTX significantly reduced Akt phosphorylation (p‐Akt), compared with RTX treatment alone (Figure F).…”
Section: Resultsmentioning
confidence: 70%
“…To further investigate the cause, focus was placed on the apoptosis signaling pathway. It has been reported that apoptosis is related to Akt activation in many cancers and targeting the PI3K/Akt pathway may suppress tumorigenesis and induce cell death . As shown, treatment combining hyperthermia and RTX significantly reduced Akt phosphorylation (p‐Akt), compared with RTX treatment alone (Figure F).…”
Section: Resultsmentioning
confidence: 70%
“…Huang [40], Zeng [41], and Zuo [42] et al demonstrated that the expression levels of TIMP1 may be negatively correlated with the prognosis of COAD patients. Song et al [43] found that TIMP1 knockdown could result in decreased proliferation, migration, and invasion as well as increased apoptosis in vitro, whereas there is weakened tumorigenesis and metastasis in vivo via the FAK-PI3K/Akt and MAPK pathways. The elevated TIMP1 levels in serum were related to lower tumor grade and shorter overall survival times of CRC patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inhibitors of metalloproteases (TIMPs) have been implicated in tumourigenesis. TIMP1 overexpression is associated with advanced stages of CRC [109]. IHC studies have demonstrated a significant correlation between TIMP2 expression in inflammatory cells, increasing tumor size, lymph node involvement and presence of metastasis [110].…”
Section: Tissue Inhibitors Of Metalloproteasesmentioning
confidence: 99%